Internal solitary wave refraction at Dongsha Atoll, South China Sea. Issue 12 (20th June 2013) - Li, Xiaofeng; Jackson, Christopher R.; Pichel, William G.
Abstract: [1] Internal solitary waves (ISWs) are regularly generated at the Luzon Strait, propagate westward into the South China Sea, and dissipate on the continental shelf after persisting for more than 4 days. The Dongsha Atoll stands in the middle of their propagation path and the incident ISW bifurcates as it interacts with, and passes the atoll. As the two arms meet on the western side of Dongsha, they produce complex patterns from nonlinear internal wave interactions. In this study, new satellite observations are presented that show unusual ISW refraction patterns at the Dongsha Atoll. In these satellite images the incident wave is located on one side of Dongsha, and the portion of the wave closest to the atoll continues to propagate around the atoll circularly, while the remaining portion of the arm continues its westward propagation. The process is adequately modeled using a function relating ISW phase speed to ocean depth. Key Points: Unusual IW refraction at Dongsha Atoll is observed by satellite images A conceptual model is implemented to understand the mechanism of IW refraction The rare occurrence of refracted IW at atoll is discussed